COVID-19: DO MEDICAL STUDENTS KNOW, BOTHER ABOUT, AND PRACTISE PREVENTIVE MEASURES IN MALAYSIA? - Md Mizanur Rahman; Mohaamad Shaah; Yuggesh Kumar; Sumeetha Marimuthu; Mithrra Sundaram; Shaundari Muniandy; Mahanagaraani Yogeswaran; Shamilaa Bala Krishnan Muthiah (Malaysian Journal of Public Health Medicine, 2020)
Since December 2019, a novel coronavirus disease (COVID-19) creates a global threat. Medical students are more susceptible to be infected by the virus. This study aimed to assess COVID-19 related knowledge, attitude towards COVID-19, and preventive behaviours against COVID-19 among medical students within the first month of the onset of the outbreak in Malaysia. We collect data from medical students using an online Google survey form. Out of 696 students, 467 responded to the questionnaire. The analysis revealed that the mean percentage of knowledge was (85.04), attitude (84.12), and preventive practice (77.75) respectively. Hierarchical multiple linear regression analysis revealed that living with family (p<0.01) and knowledge of COVID-19 (p<0.001) appeared to be important predictors of attitude toward COVID-19. However, gender (p<0.001), living status (p<0.001), frequency of travel during movement control order (p<0.01), attitude towards COVID-19 (p<0.001) have appeared significant predictors for preventive practice against COVID-19. But knowledge of COVID-19 had no impact on preventive practice against COVID-19 (p>0.05). We found a high level of COVID-19 related knowledge, attitude, and preventive practice against COVID-19 among medical students. A sustained knowledge, attitude, and preventive behavioural strategy could play an ingredient in upholding the student’s learning and practice against any disease like COVID-19.